2021
DOI: 10.1371/journal.pone.0260522
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of necrotizing enterocolitis by conditioned medium derived from human amniotic fluid stem cells

Abstract: Purpose Necrotizing enterocolitis (NEC) is one of the most distressing gastrointestinal emergencies affecting neonates. Amniotic fluid stem cells (AFSC) improve intestinal injury and survival in experimental NEC but are difficult to administer. In this study, we evaluated whether conditioned medium (CM) derived from human AFSC have protective effects. Methods Three groups of C57BL/6 mice were studied: (i) breast-fed mice as control; (ii) experimental NEC mice receiving PBS; and (iii) experimental NEC mice re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Various treatment strategies have been proposed for NEC, but recently, MSC therapy has become the preferred option due to its pronounced therapeutic efficacy. There is evidence that therapeutic effects can be achieved not only via the transplantation of stem/progenitor cells but also through the use of a conditioned culture medium containing cell secretomes and EVs [ 194 , 195 , 196 ]. In an experimental model of NEC, it was shown that bone marrow-derived MSCs and their exosomes contributed to a significant reduction in the development of the pathological process and maintained the integrity of the intestinal mucosa and its physiological permeability.…”
Section: Experimental Studies Of Evs As Therapeutic Tools For Neonata...mentioning
confidence: 99%
“…Various treatment strategies have been proposed for NEC, but recently, MSC therapy has become the preferred option due to its pronounced therapeutic efficacy. There is evidence that therapeutic effects can be achieved not only via the transplantation of stem/progenitor cells but also through the use of a conditioned culture medium containing cell secretomes and EVs [ 194 , 195 , 196 ]. In an experimental model of NEC, it was shown that bone marrow-derived MSCs and their exosomes contributed to a significant reduction in the development of the pathological process and maintained the integrity of the intestinal mucosa and its physiological permeability.…”
Section: Experimental Studies Of Evs As Therapeutic Tools For Neonata...mentioning
confidence: 99%
“…Treatment with CM was associated with increased stem cell activity and recovery from NEC, similar to the effect of AFSCs-derived exosomes. While the composition of this CM differs from the physiological secretome as produced by AFSCs, AFSC-CM holds important cellular information (e.g., mRNA, miRNA, DNA, proteins, and EVs) ( 39 ).…”
Section: Amniotic Fluid-based Therapy In Neonates With Necrotizing En...mentioning
confidence: 99%
“…In NEC, a decrease in Treg cells disrupts the equilibrium and increases proinflammatory Th17 cell response ( 44 ). However, when AFSCs are administered, TLR4-mediated signaling is inhibited ( 44 ) and inflammatory markers such as TNFα and IL-6 are significantly decreased ( 45 ).…”
Section: Mechanism Of Action: Amniotic Fluid Stem Cell Potential In Necmentioning
confidence: 99%
“…A recent study demonstrated that administration of human AFSC conditioned medium (hAFSC-CM) improved NEC survival and reduced intestinal injury ( 45 ). Specifically, intestinal mucosal inflammation and epithelial apoptosis were significantly reduced.…”
Section: Afsc Derivatives In Necmentioning
confidence: 99%